2023
DOI: 10.1093/brain/awad113
|View full text |Cite
|
Sign up to set email alerts
|

Altered nucleus accumbens functional connectivity precedes apathy in Parkinson’s disease

Abstract: Work in animal and human neuroscience has identified neural regions forming a network involved in the production of motivated, goal-directed behaviour. In particular, the nucleus accumbens and anterior cingulate cortex are recognized as key network nodes underlying decisions of whether to exert effort for reward, to drive behaviour. Previous work has convincingly shown that this cognitive mechanism, known as effort-based decision making, is altered in people with Parkinson’s disease with a syndrome of reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 100 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…42 In PD patients, reduced functional connectivity and striatal neurodegeneration precede the emergence of motivational symptoms. 16,17 This suggests that disruption to frontostriatal circuit synchrony may impair reward valuation and lead to the emergence of motivational and mood symptoms. Different subregions of the ventral striatum have been shown to have dissociable contributions to the motivational versus hedonic components of the affective processing of reward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 In PD patients, reduced functional connectivity and striatal neurodegeneration precede the emergence of motivational symptoms. 16,17 This suggests that disruption to frontostriatal circuit synchrony may impair reward valuation and lead to the emergence of motivational and mood symptoms. Different subregions of the ventral striatum have been shown to have dissociable contributions to the motivational versus hedonic components of the affective processing of reward.…”
Section: Discussionmentioning
confidence: 99%
“…15 Loss of pre-synaptic dopaminergic projections to the striatum and reduced functional connectivity in this region are associated with increased apathy and anhedonia in PD. 16,17 This may explain why mood changes in PD are frequently associated with motor fluctuations, or “ON/OFF” dopamine states 18 , and suggests depression in PD could be related to dopaminergic deficits which mediate specific neurocognitive processes.…”
Section: Introductionmentioning
confidence: 99%
“… 42 As serotonin promotes choice persistence, 32 upregulation of serotonergic systems could be an explanation for how our non-apathy group could continue to exploit, despite impaired encoding of a decision outcomes. A ‘double-hit’ phenomenon would be consistent with recent longitudinal imaging by Morris et al ., 99 where loss of functional connectivity between dACC and ventral striatum in non-apathetic PD patients preceeded the clinical expression of a demotivated state.…”
Section: Conclusion and Future Predictionsmentioning
confidence: 99%
“…It has been indicated that PD patients with apathy display a widespread decrease in the extra-striatal uptake of dopamine transporters compared to those without apathy, as well as a lower longitudinal dopamine transporter uptake [22]. Abnormal functional connectivity between the anterior cingulate cortex and nucleus accumbens has been demonstrated to precede apathy in patients with PD [23], and apathy has been shown to be 2.6 more common in non-PD individuals carrying GBA mutations compared to healthy controls [24]. Visual hallucinations in patients with PD have also been associated with specific dopamine receptor single-nucleotide polymorphisms (SNPs) [25].…”
Section: Introductionmentioning
confidence: 99%